Post-Graduation Work Visas and Loopholes: Insights into Support Provision for International Graduates from the Perspectives of Migration Agents, Universities, and International Graduates. (August 2022) - Tran, Ly Thi; Bui, Huyen; Tan, George; Rahimi, Mar
Background: Major host countries of international students such as Australia, Canada, New Zealand, the UK, and the US have introduced post-study work rights as a strategic policy to both enhance their destination attraction and support international students' post-graduation work experiences. While this policy is generally welcomed by both host institutions and international students, little is known about the support mechanism for the growing cohort of international student graduates who stay in their countries of study on temporary graduate visas, especially in relation to major concerns such as post-graduation work, visa application, and migration pathways.Objective: This article fills an important gap in the existing literature. It aims to assess the role of universities in supporting their international alumni on temporary visas.Research Design: It is derived from a study that includes 50 interviews with university staff, agents, and international graduates. It uses positioning theory as a conceptual framework.Results: The findings of the study raise concerns about the scope of university advice. It reports loopholes which legitimize the practices of migration agents to the conditions that enable them to exercise their exclusive rights in providing work-migration nexus advice to international students and graduates, making this cohort vulnerable to exploitation of unethical agents. The study provides the evidence base to develop recommendations for related stakeholders in improving the post-graduation experiences of international student graduates who remain in the host countries on temporary visas.